The United Nations comes out!: the construction of sexual orientation in the UN human rights institutions / organs (1983-2011). - Paredes Minango, Carlos Andrés (2013)
Having a constructivist approach to knowledge through regime theory and international organization, this work investigates the construction of sexual orientation at the UNOHCHR. I make use of discourse analysis to explore how this topic has been portrayed in Human Rights Committee decisions and Human Rights Council documents dealing with this theme from 1983 to 2012. The main argument put forward in this thesis is that the United Nations Organization acts as a structure, exercising tactical or organizational power; and as an agent exercising structural power when constructing sexual orientation at the Human Rights specialized agencies. The works concludes that in the last couple of years there has been a significant discursive change regarding what is said about sexual orientation in UN documents: how sexual orientation is characterized.